Primary evaluation of COF-based mixed matrix membranes to antifouling property - Nur Azizah, Johari; Noor Yahida, Yahya; Norhaniza, Yusof; Siti Nur Syazana, Zakaria (Elsevier Ltd, 2023)
Nowadays, anaerobic membrane bioreactors (AnMBRs) are one of the considerable wastewater treatment technologies. However, the performance of AnMBRs in wastewater treatment is faded due to the membrane fouling issue. Due to that concern, it gives a reason to find a material with high quality properties to prepare an antifouling membrane for the application in AnMBRs. In this present study, a new ultrafiltration (UF) membrane incorporated covalent organic framework (COF) was successfully constructed by interfacial polymerization method. A mixed-matrix membranes (MMMs) in various concentrations of COF range of 0 to 1 wt% was prepared and characterized by SEM, XRD, FTIR and AFM analysis. The analysis has confirmed the incorporation of the COF to the UF membrane. The effect of various COF concentration towards the antifouling property of the prepared membranes were evaluated. The results show, the increasing of COF concentration from 0 to 1 wt% has led to the increasing in the rejection rate from 26.11% to 95.87%. Besides, the membrane hydrophilicity significantly improved by 30.53%, when the water contact angle decreased from 66.94° to 46.50°. These results suggested that the PES/COF MMMs has great potential to offer an efficient separation with superior antifouling membrane for AnMBRs.